Quantitation of a Novel Engineered Anti-infective Host Defense Peptide, ARV-1502: Pharmacokinetic Study of Different Doses in Rats and Dogs - Brakel, Alexandra; Volke, Daniela; Kraus, Carl N.; Otvos, Laszlo; Hoffmann, Ralf (Frontiers in Chemistry, 2019)
The designer proline-rich antimicrobial peptide (PrAMP) Chex1-Arg20 amide (ARV-1502) is active against Gram-negative and Gram-positive pathogens in different murine infection models when administered parenterally and possesses a wide therapeutic index. Here we studied the pharmacokinetics of ARV-1502 for the first time when administered intramuscularly or intravenously (IV) in Sprague Dawley rats and Beagle dogs. First, a specific and robust quantitation method relying on parallel reaction monitoring (PRM) using a high-resolution hybrid quadrupole-Orbitrap mass spectrometer coupled on-line to reversed-phase uHPLC was established and validated. The limit of detection was 2 ng/mL and the limit of quantitation was 4 ng/mL when spiked to pooled rat and dog plasma. When ARV-1502 was administered IV at doses of 75 and 250 µg/kg in dogs and rats, the plasma concentrations were 0.7 and 3.4 µg/mL two minutes post administration, respectively. ARV-1502 plasma concentrations declined exponentially reaching levels between 2 and 4 ng/mL after two hours. Intramuscular administration of 0.75 mg/kg in dogs and 2.5 mg/kg in rats resulted in a different pharmacokinetics profile. The plasma concentrations peaked at 15 min post-injection at 1 µg/mL(dogs) and 12 µg/mL (rats) and decreased exponentially within three hours to 4 and 16 ng/mL, respectively. The initial plasma concentrations of ARV-1502 and the decay timing afterwards indicated that the peptide circulated in the blood stream for several hours, at some point above the minimal inhibitory concentration against multidrug-resistant Enterobacteriaceae, with blood concentrations sufficient to suppress bacterial growth and to modulate the immune system.